NILAI-NILAI PENDIDIKAN ISLAM MELALUI KEGIATAN PEMBACAAN SURAT AL-KAHFI DAN PROGRAM AL-QARDH UNTUK MENINGKATKAN SIKAP EMPATI ANTAR SESAMA DI DUSUN KATIR DESA KETRO TULAKAN - Dewi Lestari; Septyana Tentiasih (Jurnal Pendidikan Islam, 2024)
The aim of this research is to provide an understanding of the importance of Islamic educational values through the habitual activity of reading Surah Al-Kahfi and Al-Qardh which have many benefits and positive impacts. This research uses interview and observation methods so that researchers directly observe the location of the activity to obtain relevant data results. Researchers can interview sources and native residents of the location, as well as see community phenomena directly. This type of research is called qualitative research using a phenomenological approach. Based on the results of this research data, the Al-Kahf surah reading program which is consistently read every Friday and accompanied by the Al-Qardh program can create renewal in society about the importance of Islamic educational values to increase empathetic attitudes